Фактори ризику післяопераційного делірію в некардіальній хірургії - Демитер, Інна Миколаївна; Воротинцев, Сергій Іванович; Доля, Олег Сергійович; Демитер, И. Н.; Воротынцев, С. И.; Доля, О. С.; Demiter, I. M.; Vorotintsev, S. I.; Dolya, O. S. (My University, 2020)
Післяопераційний делірій (ПОД) – гостре ускладнення після хірургічних втручань, яке може виникнути у пацієнтів будь-якого віку, від дітей до літніх людей. Вважається, що люди похилого віку мають підвищений ризик розвитку ПОД, за рахунок сукупності когнітивного дефіциту, супутньої патології, крихкості, полімедикації, гіпотрофії та старіння. Мета. Оцінити інцидентність ПОД та визначити вплив факторів ризику на розвиток ПОД. Об’єкт і методи. В одноцентрове проспективне дослідження були послідовно включені 46 пацієнтів похилого віку, яким виконувалися оперативні втручання на органах черевної порожнини в ургентному порядку. Пацієнти, що мали в анамнезі черепномозкову травму або інсульт з неврологічними порушеннями у вигляді сенсорно-моторної афазії та геміплегії були виключені з дослідження. Пацієнтам визначали рівень зношеності, ризик виникнення ПОД, когнітивних порушень, рівень седації та ажитації, проводили скринінг делірію. Статистичний аналіз проведено за допомогою програми «STATISTICA for Windows 13» (StatSoftInc., №JPZ804I382130ARCN10-J). Послеоперационный делирий (ПОД) – острое осложнение после хирургических вмешательств, которые могут возникнуть у пациентов любого возраста, от детей до пожилых людей. Считается, что пожилые люди имеют повышенный риск развития ПОД за счет совокупности когнитивного дефицита, сопутствующей патологии, хрупкости, полимедикации, гипотрофии и старения. Цель. Оценить инцидентность ПОД и определить влияние факторов риска на развитие ПОД. Объект и методы. В одноцентровое проспективное исследование были последовательно включены 46 пациентов пожилого возраста, которым выполнялись оперативные вмешательства на органах брюшной полости в ургентном порядке. Пациенты, имевшие в анамнезе черепно-мозговую травму или инсульт с неврологическими нарушениями в виде сенсорно-моторной афазии и гемиплегии были исключены из исследования. Пациентам определяли степень износа, риск возникновения ПОД, когнитивных нарушений, уровень седации и ажитации, проводили скрининг делирия. Статистический анализ проведен с помощью программы «STATISTICA for Windows 13» (StatSoftInc., №JPZ804I382130ARCN10-J). Postoperative delirium (POD) is an acute complication after surgery that can occur in patients of any age, from children to the elderly. It is believed that the elderly have an increased risk of developing POD, due to a combination of cognitive deficits, comorbidities, fragility, polymedicine, malnutrition and aging. The aim of the study was to assess the incidence of POD and determine the impact of risk factors on the development of POD. Object and methods. After passing the Commission on Bioethics at Zaporizhzhya State Medical University and obtaining informed consent, 46 elderly patients who underwent surgery on the abdominal organs in an urgent manner were consistently included in the one-center prospective study. Results. According to the results of our study, POD was detected in 35% of cases (n = 16) among patients who underwent emergency surgery. In our study, the analysis of the ROC curve showed that the age of ≥78 years is the optimal threshold age for the development of POD with a sensitivity of 56.2% and a specificity of 82.1%. The score on the Mini-Cog scale of 3 points is the optimal threshold level for the development of POD with a sensitivity of 87.5% and a specificity of 53.5%. To determine the risk of POD using the Delphi scale, analysis of the ROC curve showed that a score of 7 points is the optimal threshold level for the development of POD with a sensitivity of 81.25% and a specificity of 78.57%. In our study, the analysis of the ROC curve showed that the assessment on the scale of wear ≥3 points is the optimal threshold level for the development of POD with a sensitivity of 68.7% and a specificity of 53.5%. According to the results of the analysis of the ROC-curve of leukocytosis, 13.4 *109/l is the optimal threshold level of leukocytes for the development of POD with a sensitivity of 57.1% and a specificity of 85.2%. The use of narcotic analgesics for postoperative analgesia (odds ratio 5.3, 95%, confidence interval 1.2-23.8) was one of the independent risk factors for POD. Conclusions. POD was recorded in 35% of cases among patients who underwent non-cardiac surgery in an urgent manner. Dementia, age 78 years and older, fragility greater than 3 points, and postoperative analgesia with narcotic analgesics were independent risk factors for POD.
Факторы риска послеоперационного делирия в некардиальной хирургии
Risk factors of postoperative delirium in noncardial surgery
Keywords: післяопераційний делірій; пацієнти похилого віку; фактори ризику; послеоперационный делирий; пациенты пожилого возраста; факторы риска; postoperative delirium; elderly patients; risk factors